Women's involvement in family firms: Progress and challenges for future research. Issue 4 (December 2017) - Campopiano, Giovanna; De Massis, Alfredo; Rinaldi, Francesca Romana; Sciascia, Salvatore
Abstract: This article reviews research on women's involvement in family firms according to a drivers-behaviors-outcomes framework. Through a systematic review, we analyze and organize the content of 87 academic articles according to the type of involvement of women in family business, i.e. entrepreneurial entry, succession, career dynamics, and presence in family firms. We identify the drivers and outcomes of women's involvement in family firms at the firm, family, and individual level of analysis, as well as the contextual factors that may influence the aforementioned elements. Drawing on these findings, we identify relevant research gaps, propose a number of future research directions aimed at bridging these gaps, and suggest unexplored research avenues.